2018
DOI: 10.1007/s00296-018-4018-0
|View full text |Cite
|
Sign up to set email alerts
|

Association between memory B-cells and clinical and immunological features of primary Sjögren’s syndrome and Sicca patients

Abstract: B-cells play a pivotal role in primary Sjögren's syndrome (pSS) pathogenesis. We aim to (1) evaluate the distribution of B-lymphocyte subpopulations in pSS and Sicca patients, (2) establish cut-off points that discriminate pSS from controls, (3) evaluate the association between memory B-cells and phenotypic features in pSS. We included 57 pSS patients, 68 Sicca and 24 healthy controls. Circulating B-cells were characterized by flow cytometry as naïve and memory subsets and classified from Bm1 to Bm5. Compared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 38 publications
1
8
0
Order By: Relevance
“…This of interest, because clinical data of patients in this study suggest comparable trends, with cases in JIA-Uveitis 2 showing longer disease duration compared to the other groups. In contrast, in B cell-mediated inflammatory conditions such as Sjogren's disease longer disease duration is associated with a decrease in memory B cell subsets and a more active disease profile (37). Furthermore, although age-related changes in memory B cell subsets have been reported, the absolute number of peripheral blood naïve and memory B cell subsets both decline from ±2-4 years old until adulthood (30).…”
Section: Discussionmentioning
confidence: 99%
“…This of interest, because clinical data of patients in this study suggest comparable trends, with cases in JIA-Uveitis 2 showing longer disease duration compared to the other groups. In contrast, in B cell-mediated inflammatory conditions such as Sjogren's disease longer disease duration is associated with a decrease in memory B cell subsets and a more active disease profile (37). Furthermore, although age-related changes in memory B cell subsets have been reported, the absolute number of peripheral blood naïve and memory B cell subsets both decline from ±2-4 years old until adulthood (30).…”
Section: Discussionmentioning
confidence: 99%
“…2014; Barcelos et al. 2018). These B‐cell disturbances in SjS may represent the presence of a more immature component in transit to target organs and a shift in maturation towards the plasma cell lineage.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, there is strong evidence of unbalance of B cell subpopulations also in SS. Many authors found that memory and switched memory B cells are reduced in primary SS compared to controls (86)(87)(88), and this unbalance appears to be related to disease duration and activity (88). Saadoun et al found an increase of CD21 low/-B cells in primary SS and in particular in primary SS with lymphoproliferative disorders, suggesting a key role of this B cell population in SS related lymphomagenesis (89,90).…”
Section: Ss and B-cell Abnormalitiesmentioning
confidence: 99%
“…On the other hand, there is strong evidence of unbalance of B cell subpopulations also in SS. Many authors found that memory and switched memory B cells are reduced in primary SS compared to controls ( 86 88 ), and this unbalance appears to be related to disease duration and activity ( 88 ). Saadoun et al.…”
Section: Common Features Between Cvid and Sjögren’s Syndromementioning
confidence: 99%